Validity of ICD-10 diagnoses of overweight and obesity in Danish hospitals - Gribsholt, Sigrid Bjerge (Clin Epidemiol, 2019)
PURPOSE: Health care databases may be a valuable source for epidemiological research in obesity, if diagnoses are valid. We examined the validity and completeness of International Classification of Diseases, 10th revision [ICD-10] diagnosis coding for overweight/obesity in Danish hospitals. PATIENTS AND METHODS: We linked data from the Danish National Patient Registry on patients with a hospital diagnosis code of overweight/obesity (ICD-10 code E66) with computerized height and weight measurements made during hospital contacts in the Central Denmark Region Clinical Information System. We computed the positive predictive value (PPV) of the IDC-10 diagnosis of overweight/obesity, using a documented body mass index (BMI) ≥25 kg/m(2) as gold standard. We also examined the completeness of obesity/overweight diagnosis coding among all patients recorded with BMI ≥25 kg/m(2). RESULTS: Of all 19,672 patients registered with a first diagnosis code of overweight/obesity in the National Patient Registry, 17,351 patients (88.2%) had any BMI measurement recorded in the Central Denmark Region Clinical Information System, and 17,240 patients (87.6%) had a BMI ≥25 kg/m(2), yielding a PPV of 87.6% (95% CI: 87.2–88.1). The PPV was slightly higher for primary diagnosis codes of overweight/obesity: 94.1% (95% CI: 93.3–94.8) than for secondary diagnosis codes: 86.1% (95% CI: 85.6–86.6). The PPV increased with higher patient age: from 75.3% (95% CI: 73.8–76.9) in those aged 18–29 years to 94.7% (95% CI: 92.6–96.9) in patients aged 80 years and above. Completeness of obesity/overweight diagnosis coding among patients recorded with BMI ≥25 kg/m(2) was only 10.9% (95% CI: 10.8–11.0). CONCLUSION: Our findings indicate a high validity of the ICD-10 code E66 for overweight/obesity when recorded; however, completeness of coding was low. Nonetheless, ICD-10 discharge codes may be a suitable source of data on overweight/obesity for epidemiological research.